Reuse of the Reflective Light and the Recycle Heat Energy in Concentrated Photovoltaic System. (9th April 2013) - Chen, Hsin-Chien; Chang, Liann-Be; Lin, Ho-Thea; Jeng, Ming-Jer; Chow, Lee
Abstract : A complex solar unit with microcrystalline silicon solar cells placed around the centered GaAs triple junction solar cell has been proposed and carried out. With the same illumination area and intensity, the total resultant power shows that the excess microcrystalline silicon solar cells increase the total output power by 13.2% by absorbing the reflective light from the surface of optical collimators. Furthermore, reusing the residual heat energy generated from the above-mentioned mechanism helps to increase the output power by around 14.1%. This mechanism provides a simple method to enhance the utility rate of concentrated photovoltaic (CPV) system. Such concept can be further applied to the aerospace industry and the development of more efficient CPV solar energy applications.